The implementation of digital marketing communication strategy in cultural tourism: a case study in Yogyakarta - Clariza Orivia Ghaisani; Subhan Afifi (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2022)
Cultural tourism is one category that attracts local and foreign tourists. Various previous studies have shown that digital marketing communication media plays an essential role in influencing tourist interest in visiting tourist destinations. This study aims to analyze the implementation of digital marketing communication strategies in marketing cultural tourism with a case study of cultural tourism destinations in Yogyakarta. This study uses a case study method with indepth interviews and field observations as data collection methods. The collected data were analyzed using thematic analysis and SWOT analysis. The results showed that managers of cultural tourism destinations optimize social media such as Facebook and Instagram for promotion. Whatsapp and email are also used for more personal communication with customers. The company's systematic digital marketing communications planning system supports solid work teams and produces original content. In addition, the extensive national and international marketing network and stable institutional position, because it is a stateowned company, are the advantages of this company. The increasing public interest at home and abroad for travel, the reduced Covid-19 pandemic, and the availability of various digital promotional media are opportunities for this company. However, the technical competence of staff in managing digital marketing media still needs to be improved. In addition, the digital content production and distribution scheduling system has not been implemented strictly and consistently. The quantity and quality of digital media content are also still limited. In addition, this cultural tourism object has several external challenges, such as the emergence of various new tourist objects in Yogyakarta, which are more aggressively promoted through digital media, and the possibility of a re-emergence of the Covid-19 pandemic or other natural disasters. This paper contributes to the literature on digital marketing communications by focusing on its implementation in the context of cultural tourism.